The Effect of Mindfulness Meditation on Mental Illness among Nurse in ICU and ICCU - Debby Hatmalyakin; Yulian Wiji Utami; Titin Andri Wihastuti (Research Journal of Life Science, 2019)
Critical conditions as one of the main focused in hospital care. This condition required rapid, comprehensive and quality management that carried out by nurses especially in the treatment of cardiovascular disease. This condition caused pressure on the nurse and causes stress. This stress can be overcome by complementary and alternative therapy in the form of mindfulness meditation. The purpose of this study was to identify the effect of mindfulness meditation therapy in reducing stress on nurses in ICU and ICCU. This study is quasy experiment research design through one group pretest posttest approach with respondents were 14. The results of this study indicated that there was decreased in stress before and after intervention with p-value=0000 and stress before and 1 week after intervention with p-value=0.001. Mindfulness therapy can reduce nurse stress.